Detection of Faecal Contamination and Pathogenic Escherichia coli in Drinking Water Sources within Kumbotso Local Government Area, Kano State, Nigeria : Drinking Water Sources - Innocent Musa; Aisha Adamu Abdulhamid; Maimunat Sidi Muhammad; Masauda Muhammad Umar; Fatima Adamu; Mustapha Abdulsalam; Miracle Uwa Livinus; Tasnim Tasnim; Ernawati Ginting (STIKes Mandala Waluya Kendari, 2026)
Background: This study assessed the microbiological and physicochemical quality of drinking water sources in Kumbotso Local Government Area, Kano State, Nigeria. Methods: A total of 60 samples were collected from well water, borehole water, and sachet water (20 each). Standard microbiological and physicochemical methods were employed to determine the microbial load, coliform counts, and water quality parameters. Results: The results revealed significantly higher contamination in well and borehole water compared to sachet water. The mean total coliform count by membrane filtration was 58.42 ± 98.31 CFU/100 mL in well water and 22.75 ± 79.56 CFU/100 mL in borehole water, while sachet water showed no coliforms. Similarly, faecal coliforms were detected in well water (7.65 ± 11.78 CFU/mL) and borehole water (5.20 ± 13.65 CFU/mL), exceeding the WHO guideline of zero. Klebsiella spp. (60.0%) and Escherichia coli (23.6%) were the predominant bacterial isolates, with pathogenic E. coli prevalence of 11.54%. Molecular analysis via 16S rRNA sequencing confirmed E. coli isolates with high similarity (96–98%) to pathogenic strains. Conclusion: Physicochemical parameters were generally within WHO standards, except turbidity, which exceeded the permissible limit. These findings highlight significant public health risks associated with well and borehole water in Kumbotso LGA, necessitating regular monitoring and improved water treatment strategies.